A CoII-based metal–organic framework based on [Co6(μ3-OH)4] units exhibiting selective sorption of C2H2 over CO2 and CH4. Issue 21 (3rd May 2016) - Chen, Di-Ming; Tian, Jia-Yue; Liu, Chun-Sen; Du, Miao
Abstract : A new microporous Co II -MOF has been successfully assembled by employing isonicotinic acid as a tecton and planar Co6 clusters as SBUs, which exhibits high thermal stability and selective sorption of C2 H2 over CO2 and CH4 at room temperature. Abstract : By virtue of unique planar [Co6 (μ3 -OH)4 ] cluster units, a new microporous isonicotinate-based framework with high thermal and framework stabilities was achieved. The guest-free framework demonstrates high capacity and selectivity for C2 H2 relative to CO2 and CH4 at room temperature, which was further understood by GCMC simulation.